Problemy koncepcyjne naturalizmu redukcyjnego Quine’a - Haraburda, Michał (Filozofia Nauki, 2019)
Quine’s position is counted as a reductive naturalism. It overcomes both the traditional Cartesian-Kantian approach to philosophy and the theory of logical empiricism. In consequence, Quine turns for guidance to empirical science. Philosophical reflection turns out to be secondary and dependent on science, for it is the empirical sciences that are the only source of genuine knowledge. As a result, philosophy should be reduced, in Quine’s view, to the application of scientific methods to problems that more general than those raised within the sciences themselves. Quine’s position is criticized in this article both internally, for being inconsistent, and externally, from the point of view of non-reductive naturalism. The criticism primarily pertains to (a) the doctrine of physicalism, (b) the thought-experiment regarding the indeterminacy of translation, and (c) non-observability of the principles of naturalism.